SYEIKH M. NAFIS AL-BANJARIE'S PERSPECTIVE TAUHIDUSSIFAT EDUCATION CONCEPT IN THE BOOK AD-DURUN NAFIS - Sufyan, hadi (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2023)
Islamic basic education is tauhid. Islamic scholars tried to make the idea of the oneness of Allah as pure as possible. as the chaos that erupted in the scope of Indonesia. Even though many humans have the knowledge and are able to learn it, they ignore the Khaliq who teaches it. This study uses a qualitative methodology known as a literature review to describe and elaborate on the idea of monotheism education from the perspective of Sheikh Muhammad Nafis Al-Banjarie in Kita Ad-Durun Nafis. From the late 18th century to the early 19th century, Sheikh Muhammad Nafis al-Banjari was a Banjar scholar. In the Malay world, he is the most important figure in the field of Sufism. According to Sheikh Muhammad Nafis, education must be based on the belief that Allah is the source of knowledge. Allah, who permits and provides for human beings, is the main factor in all that we can achieve. This is because humans have a mortal nature that will vanish if given a good nature, such as Allah SWT.